Approximate Method for Solving System of Linear Fredholm Fractional Integro-Differential Equations Using Least Squares Method and Lauguerre Polynomials - Goud, Parameshwari M.; Nanware, J. A.; Holambe, T. L.; Jadhav, N. B. (Communications in Mathematics and Applications, 2023)
An attempt is made to develop approximate method to get approximate solution of system of linear Fredholm fractional integro-differential equations using Least squares and Lauguerre polynomial method. The system of linear Fredholm fractional integro-differential equations is reduced to a system of linear equations using Lauguerre polynomials. The method is implemented to obtain approximate solution of the system of Fredholm fractional integro-differential equations. The solutions are simulated using Scilab.
Keywords: System of linear Fredholm fractional integro-differential equations; Least square method; Lauguerre polynomials; Caputo derivative